Protective Effects of Chicken Egg Yolk Immunoglobulins (IgYs) against Vibrio vulnificus Infections - Ruizhao Cai; Ning Liu; Penghao Guo; Kang Liao; Mengzhi Li; Junyou Zhu; Shouyi Chen; Lei Chen; Bin Shu; Shaohai Qi (Journal of Immunology Research)
Vibrio (V.) vulnificus infection is a rare disease whose death rates exceed 50% despite aggressive antibiotic treatment and surgical debridement. The aim of this study was to assess the ability of specific anti-V. vulnificus immunoglobulins Y (IgYs) for preventing and treating V. vulnificus infections. IgYs were produced by immunizing egg laying hens with inactivated whole cell bacteria. Peritoneal cytokines, blood’s bacterial load, and survival curves were obtained from both prophylactic and therapeutic mouse models. The results showed that the specific IgYs (i) inhibited the growth of V. vulnificus in vitro, (ii) dramatically reduced the inflammatory response and blood’s bacterial load, and (iii) improved the survival rate of V. vulnificus-infected mice. These results prove that anti-V. vulnificus IgYs can be markedly effective means for the prophylaxis and the therapy of V. vulnificus infections.